GENERATION Z'S INTEREST IN ISLAMIC BANKS - Septianingsih, Rika; Busyro, Wahyi; Noudza, Rizelvi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study aims to analyze: 1) the effect of profit sharing on the interest of generation z customers using Bank Syariah Indonesia (BSI) post-merger, 2) the effect of product yields on the interest of generation z customers using Bank Syariah Indonesia (BSI) post-merger, 3) the effect of facilities results on the interest of generation z customers using Bank Syariah Indonesia (BSI) after the merger, 4) the effect of knowledge of results on the interest of generation z customers using Bank Syariah Indonesia (BSI) after the merger. The population in this study is the generation z customers of the Indonesian Islamic Bank in Pekanbaru. Samples were obtained as many as 97 respondents, with the sampling technique using non-probability sampling techniques. This research is a quantitative research with multiple linear analysis method. The results of the research from the partial t-test are: 1) Profit sharing has no effect on the interest of Generation Z customers of Bank Syariah Indonesia (BSI), by getting the value of Sig. 0.964 > 0.05. 2) The product does not affect the interest of Generation Z customers of Bank Syariah Indonesia (BSI), by obtaining a Sig. 0.474 > 0.05. 3) Facilities affect the interest of Generation Z customers of Bank Syariah Indonesia (BSI), by obtaining the value of Sig. 0.036 < 0.05. 4) Knowledge affects the interest of Generation Z customers of Bank Syariah Indonesia (BSI), by obtaining the value of Sig. 0.000 < 0.05. Of the four variables that most dominantly affect customer interest, namely knowledge.